Optimizing Junior Fried Chicken Business Production Profits Using the Fuzzy Linear Programming Method - Hasibuan, Citra Dewi; Rahmah, Mudia (Journal of Research in Mathematics Trends and Technology, 2023)
This research aims to optimize production and profits in the Junior Fried Chicken business using the Fuzzy Linear Programming (FLP) method. The data collected includes product data, raw materials, production costs, and sales profits. The author constructs a mathematical model that includes objective functions and constraints based on the data obtained. Next, the Fuzzy Linear Programming (FLP) method is used to make optimal decisions about the amount of production for each menu. It is hoped that the results of this research can help business owners optimize their production and profits.